PENERAPAN AKUNTANSI KEPERILAKUAN PADA PT. HADJI KALLA TOYOTA PINRANG (ANALISIS AKUNTANSI SYARIAH) - Kumala Dewi (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2024)
Behavioral accounting can help identify and prevent accounting fraud in companies and improve the quality of company information disclosure. The purpose of behavioral accounting is to understand human behavior in the context of accounting and finance, and to provide an understanding of how financial decisions are made. The research method used by the writer is qualitative research. Qualitative research is research that uses the background of nature, with the intention of interpreting the phenomenon that occurs and is carried out by involving various existing methods. Based on the research results obtained about the application of behavioral accounting at PT. Hadji Kalla Toyota Pinrang, Behavioral Accounting provides convenience for companies in determining steps based on existing financial reports that have a positive and significant impact on managerial performance. Behavioral accounting provides great benefits for the management of an organization or company in making decisions. Behavioral accounting can facilitate decision-making because behavioral accounting presents data on the behavior and attitude of employees before the company makes a decision so that the company knows whether its employees have reached the target or not, because basically individual attitudes can affect all processes in the company. decision making